Stroke systems of care in the Philippines: Addressing gaps and developing strategies - Collantes, Maria Epifania; Navarro, Jose; Belen, Allan; Gan, Robert (Frontiers in Neurology, 2022)
In the Philippines, the mortality from stroke during the last 10 years remains high. This paper aims to describe the gaps in stroke care and the development of stroke systems of care in the Philippines. Gaps in stroke systems of care include low number of neurologist, inadequate CT scan machines, lack of stroke training among health workers, lack of stroke protocols and pathways, poor community stroke awareness, low government insurance coverage with high out of pocket medical expenses, lack of infrastructure for EMS, inadequate acute stroke ready hospitals, stroke units and rehabilitation facilities. Although there are government programs for primary stroke prevention, the strategies are inadequate to address the stroke pandemic. The Stroke Society of the Philippines has worked with the government for nationwide and regional stroke training of health care workers, community stroke awareness, setting up acute stroke ready hospitals and acute stroke units in different areas of the country and adapting stroke protocols and pathways. Stroke registries are now utilized for quality improvement. Thrombolysis rate has improved from 1.4% in 2014–2016 to 11% in 2021 based on RES-Q database. Because of government subsidy, thrombolysis in the government hospitals is higher at 7.4% (range 4.4–16.9) compared to 4.8% (range 0–10.1) rate in private hospitals. Mechanical thrombectomy rate remained low at 0.4% of all acute ischemic stroke patients because of the cost. With limited resources, infrastructures for emergency medical service is lacking. The innovations done by other LMIC can be done in the Philippines including the use of technology to reach out to geographically isolated areas and use of mobile stroke units. Non neurologist can be trained to help treat stroke patients. Upgrading of the Philhealth insurance to cover for reperfusion therapies, adequate stroke infrastructures and network, and increase in community stroke awareness are areas for improvement in the Philippine stroke systems of care.